Analysis Factors Affect of Murabahah Margin in Sharia Commercial Banks in Indonesia - Nisa, Ainun (Jurnal Iqtisaduna, 2020)
Financing with the murabahah contract becomes the most dominating because murabahah contract is easier to use because it is obvious the split, does not require a complex analysis that benefit both parties between Islamic banks and customers. So that murabahah financing becomes the main product in Islamic banking in Indonesia. The research purpose to analysis and determine a direct effect of operating expense and third fund party to murabahah margin in sharia commercial banks in Indonesia. The period use in this research is 5 years, starting from 2014 to 2018. The type of this research was an causal research to show the direction in the relation between operating expense and third fund party to murabahah margin also to measure the strength of the relation between two or more variables. The population in this research a number of 14 islamic commercial banks that have been and are still registered with the Financial Services Authority in 2014 to 2018. The data analysis technique used in purposive sampling and obtained a sample of 12 islamic commercial banks. The data analysis technique used is multiple linear regression using eviews version 9. The results showed that the operating expense had a negative and significant effect on murabahah margin and third fund party had a positive and significant effect on murabahah margin.